Early and “Middle” Cretaceous Iguanodonts in Time and Space - Carpenter, K.; Ishida, Y. (Journal of Iberian Geology, 2010)
Recent discoveries of diverse iguanodonts throughout the Cedar Mountain Formation (Utah, USA) have led us to assess the global diversity of Early Cretaceous iguanodonts. The record in England is more diverse than previously recognized due to Iguanodon being a wastebasket genus throughout the Twentieth Century. Several new taxa, previously recognized as generically distinct by Harry Grovier Seeley, are named. The spatial and temporal distributions of iguanodonts are plotted on global maps as a key to understanding the origin of the Cedar Mountain Formation iguanodonts.